Management of residual masses in testicular germ cell tumors. Issue 4 (3rd April 2019) - Heidenreich, Axel; Paffenholz, Pia; Nestler, Tim; Pfister, David
ABSTRACT: Introduction : About 50% of all patients with advanced testicular cancer demonstrate residual retroperitoneal or extraretroperitoneal masses. About two thirds of the masses harbour necrosis/fibrosis only whereas as about 10% and 40% harbour vital cancer or teratoma. Appropriate therapy will result in a high cure rate if performed properly. Areas covered : This review article covers the indication, the surgical technique and the oncological outcome of PC-RPLND and resection of extraretroperitoneal residual masses following chemotherapy in patients with advanced testis cancer. Expert commentary : Postchemotherapy retroperitoneal lymph node dissection (PC-RPLND) plays an integral part of the multimodality treatment in patients with advanced testicular germ cell tumours. Patients with nonseminomas, residual masses < 1cm and good prognosis can undergo active surveillance. In all other cases, PC-RPLND with or without resection of adjacent organs needs to be performed for curative intent. PC-RPLND requires a complex surgical approach and should be performed in experienced, tertiary referral centres only.